Extracellular vesicles from plasma have higher tumour RNA fraction than platelets. Issue 1 (25th March 2020) - Brinkman, Kay; Meyer, Lisa; Bickel, Anne; Enderle, Daniel; Berking, Carola; Skog, Johan; Noerholm, Mikkel
ABSTRACT: In addition to Circulating Tumour Cells (CTCs), cell‐free DNA (cfDNA) and Extracellular Vesicles (EVs), the notion of "Tumour‐Educated Platelets" (TEP) has recently emerged as a potential source of tumour‐derived biomarkers accessible through blood liquid biopsies. Here we sought to confirm the suitability of the platelet blood fraction for biomarker detection in comparison to their corresponding EV fraction. As publications have claimed that tumour RNA and other tumour‐derived material are transferred from tumour cells to the platelets and that tumour‐derived transcripts can be detected in platelets, we chose to focus on RNA carrying a mutation as being of bona fide tumour origin. After informed consent, we collected prospective blood samples from a cohort of 12 melanoma patients with tissue‐confirmed BRAF V600E mutation. Each blood specimen was processed immediately post collection applying two published standard protocols in parallel selecting for EVs and platelets, respectively. The RNA of each fraction was analysed by a highly sensitive ARMS RT‐qPCR enabling the quantification of the mutant allele fraction (%MAF) of BRAF V600E down to 0.01%. In a direct comparative analysis, the EV fraction contained detectable BRAF V600E in 10 out of 12 patients, whereas none of the patient platelet fractions resulted in a mutant allele signal. The platelet fraction of all 12 patients contained high amounts of wild‐type BRAF signal, but no mutation signal above background was detectable in any of the samples. Our observations suggest that the phenomenon of tumour RNA transfer to platelets occurs below detection limit since even a very sensitive qPCR assay did not allow for a reliable detection of BRAF V600E in the platelet fraction. In contrast, EV fractions derived from the same patients allowed for detection of BRAF V600E in 10 of 12 blood specimens.